New Perspectives on Genetic Prediction for Pediatric Metabolic Associated Fatty Liver Disease - Lin, Yu-Cheng; Wu, Chi-Chien; Ni, Yen-Hsuan (Frontiers in Pediatrics, 2020)
Nonalcoholic fatty liver disease (NAFLD), a spectrum of progressive hepatic disease, has become a public health issue in obese children and adolescents. NAFLD is a complex metabolic disease strongly associated with obesity and insulin resistance. It is not known why not every obese subjects develop NAFLD. Different ethnic/racial groups display differences in NAFLD prevalence, indicating genetic factor plays a role. In the past two decades, sequence variations in genetic loci, including PNPLA3, TM6SF2, GCKR, MBOAT7, HSD17B13, etc. have been shown to confer susceptibility to NAFLD in children and adults. Epigenetic alterations interacting with genetic variations further shape an individual’s susceptibility to NAFLD. This review article provides an updated viewpoint of genetic predictors related to pediatric NAFLD. We discuss whether these NAFLD susceptible genes can be clinically used for risk stratification and personalized care. In view of the current epidemic of NAFLD worldwide, it is necessary to predict which children with NAFLD progress rapidly and need earlier intervention. In the future, comprehensive analysis of personalized genetic and environmental factors may help doctors accurately assess the risk of children with NAFLD and adopt precise treatment.